Synergistic effect of light and temperature on growth and bio-chemical composition of Chlorella sorokiniana cultures - Silva Benavides, Ana Margarita (2025)
This study investigated the combined effects of light intensity and temperature on the 13 growth and biochemical composition of Chlorella sorokiniana (Chlorophyceae) under con-14 trolled laboratory conditions. The cultures were exposed to two continuous photon flux 15 densities (100 and 200 μmol m⁻² s⁻¹) and six different temperatures (20, 25, 30, 35, 40, 16 45 °C). At a light intensity of 100 μmol m⁻² s⁻¹, the highest attained volumetric productivity 17 was 16.92 mg DW L⁻¹ h⁻¹ at 25 °C, resulting in a mean final biomass density of 3.25 g DW 18 L⁻¹ after 8 days of cultivation. In contrast, at 200 μmol m⁻² s⁻¹, there were notable differences 19 in growth performance, with maximum biomass volumetric productivity reaching 31.4 mg 20 DW L⁻¹ h⁻¹ at 30 °C and a final biomass density of 6.08 g DW L⁻¹. The optimal temperature 21 for growth depended strongly on light intensity. Cultures at 20 °C thrived at 100 μmol m⁻² 22 s⁻¹ but showed negligible growth at 200 μmol m⁻² s⁻¹. No growth occurred at 45 °C under 23 either light intensity. Furthermore, temperature significantly affected biomass composition, 24 affecting both fatty acid and amino acid profiles. These findings provide valuable insights 25 for optimizing the cultivation of C. sorokiniana outdoors.